2007
DOI: 10.1128/jb.00809-07
|View full text |Cite
|
Sign up to set email alerts
|

MglA Regulates Francisella tularensis subsp. novicida ( Francisella novicida ) Response to Starvation and Oxidative Stress

Abstract: MglA is a transcriptional regulator of genes that contribute to the virulence of Francisella tularensis, a highly infectious pathogen and the causative agent of tularemia. This study used a label-free shotgun proteomics method to determine the F. tularensis subsp. novicida (F. novicida) proteins that are regulated by MglA. The differences in relative protein amounts between wild-type F. novicida and the mglA mutant were derived directly from the average peptide precursor ion intensity values measured with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 48 publications
5
79
0
Order By: Relevance
“…Cumulatively, these observations suggest that expression of the genes previously associated with growth in vivo is also a normal part of log-phase growth in vitro and that inhibition of this expression (either by growth in MHB, as shown here, or by mutation of MglA [18]) has detrimental effects on bacterial growth/physiology. BHI-grown F. tularensis cells most closely resemble extracellular M-grown bacteria.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cumulatively, these observations suggest that expression of the genes previously associated with growth in vivo is also a normal part of log-phase growth in vitro and that inhibition of this expression (either by growth in MHB, as shown here, or by mutation of MglA [18]) has detrimental effects on bacterial growth/physiology. BHI-grown F. tularensis cells most closely resemble extracellular M-grown bacteria.…”
Section: Resultsmentioning
confidence: 94%
“…For IglB, the signal for M-grown bacteria was compared to that for BHI-grown cells. (2,5,8,18,24). To determine if growth in BHI was stimulating any MglAindependent changes, we also examined the phenotype(s) of an mglA mutant in this medium.…”
Section: Resultsmentioning
confidence: 99%
“…Stress-induced (p)ppGpp production in Helicobacter pylori is required for survival during acid exposure and aerobic shock (Mouery et al, 2006;Wells & Gaynor, 2006), conditions typically encountered during the course of infection. In Francisella, intracellular replication and virulence are dependent on MglA and SspA, which regulates the FPI (Guina et al, 2007;Nano & Schmerk, 2007;Charity et al, 2007). In this study, we have identified a global regulatory system that plays a role in F. novicida virulence, where a relA mutant had reduced survival in macrophage-like cells, and was attenuated more than 100-fold in a BALB/c mouse model.…”
Section: Discussionmentioning
confidence: 90%
“…77,2009 CHARACTERIZATION OF FRANCISELLA TRANSPOSON MUTANTS 1333 carB mutants in MDM was not achieved unless uracil was added to the tissue culture medium at the time of infection or shortly thereafter. Because we also found that IglC levels are normal in mutant 9H5, which contains one intact and one disrupted copy of iglC, and this strain exhibits no apparent virulence defects, it is likely that uracil deficiency also alters the expression of other, as-yet-unidentified virulence genes outside the iglABCD operon or the FPI, perhaps via effects on key regulatory factors, such as MglA, SspA, or FevR (9,13,15,17,37,47). Our data also suggest that either sustained access to uracil or higher concentrations of this nutrient are required for intracellular replication, reminiscent of a study by Fortier et al which demonstrated that the elevation of phagosome pH by using NH 4 Cl or related agents ablates LVS growth in murine peritoneal macrophages and enhances phagocytic killing by preventing bacterial access to transferrin iron (31).…”
Section: Discussionmentioning
confidence: 96%